Adaptability and agronomic performance evaluation of mungbean (Vigna radiata (L.) Wilczek) varieties under non-inoculated and inoculated rhizobium bacteria conditions - Delie,Shiferaw Mebrat; Adamu,Teferi Alem; Andualem,Abebaw Mulugeta (PeerJ, 2025)
Background Because of its high selling price and low cost of production, farmers in the Central Gondar Zone showed great interest in mungbean production. However, the best-adapted varieties and the effectiveness of commercial Rhizobium inoculants were not determined. Hence, a study was conducted for two consecutive years to evaluate the adaptability and agronomic performances of mungbean varieties under non-inoculated and inoculated conditions. Methods A factorial combination of five mungbean varieties (Shewarobit, NVL-1, Rasa, Boreda, and Arkebe) and two inoculation levels were arranged in randomised complete block design with three replications. Data concerning flowering and maturity, nodulation, plant height, number of main branches and pods, hundred seed weight, biological and seed yields, and harvest index were collected and analyzed using R software. Results The study provided valuable insights into how variety and inoculation affect mungbean growth and yield. Inoculated seeds of Rasa, Boreda, and Arkebe took longer to flower (42.00, 40.17, and 32.33 days) and mature (86.33, 85.67, and 74.67 days), but in return, they produced more nodules (5.37, 4.83, and 2.77), branches (6.97, 6.75, and 6.45), and pods (11.83, 10.73, and 11.27) than their non-inoculated counterparts. However, no significant differences were seen for Shewarobit and NVL-1 varieties. The 2021 experiment outperformed 2022, showing higher nodules, pods, harvest index, and both biological and seed yields. Variety also played a significant role, influencing stand count, plant height, hundred seed weight, and harvest index. In 2021, the interaction of variety and inoculation affected biological and seed yields, while in 2022, only variety did. Rhizobium inoculation showed inconsistent effects on mungbean yield, suggesting the need for further investigation. The top performers in seed yield were Shewarobit (660.90–1,214.74 kg ha−1) and NVL-1 (532.35–1,097.78 kg ha−1), followed closely by Rasa (521.99–1,095.00 kg ha−1) and Boreda (546.70–1,106.63 kg ha−1), with Arkebe (367.85–606.88 kg ha−1) yielding the lowest. Conclusion Mungbean farmers in the Central Gondar Zone should prioritize Shewarobit and NVL-1 for the highest seed yields, with Rasa and Boreda as strong alternatives.
Keywords: Adaptability; Biofertilizers; Inoculation; Mungbean varieties; Rhizobium bacteria